Dysphagia and shortness-of-breath as markers for treatment failure and survival in oropharyngeal cancer after radiation. (March 2023) - Wang, Jarey H.; Salama, Vivian; McCoy, Lance; Dede, Cem; Ajayi, Temitayo; Moreno, Amy; Mohamed, Abdallah S.R.; Hutcheson, Katherine A.; Fuller, Clifton David; van Dijk, Lisanne V.; ,
Highlights: Patient reported symptoms 3–6 months after radiation associate with key outcomes. Severity of dysphagia and dyspnea associates with survival and treatment failure. Composite 3-symptom score associates with survival and treatment failure. Symptom associations with outcome were also present in HPV-positive cohort. Abstract: Background: Post-treatment symptoms are a focal point of follow-up visits for head and neck cancer patients. While symptoms such as dysphagia and shortness-of-breath early after treatment may motivate additional work up, their precise association with disease control and survival outcomes is not well established. Methods: This prospective data cohort study of 470 oropharyngeal cancer patients analyzed patient-reported swallowing, choking and shortness-of-breath symptoms at 3-to-6 months following radiotherapy to evaluate their association with overall survival and disease control. Associations between the presence of moderate-to-severe swallowing, choking and mild-to-severe shortness-of-breath and treatment outcomes were analyzed via Cox regression and Kaplan-Meier. The main outcome was overall survival (OS), and the secondary outcomes were local, regional, and distant disease control. Results: The majority of patients (91.3%) were HPV-positive. Median follow-up time was 31.7 months (IQR: 21.9–42.1). Univariable analysis showed significant associations between OS and all three symptoms of swallowing, choking, and shortness-of-breath. A composite variable integrating scores of all three symptoms was significantly associated with OS on multivariable Cox regression (p = 0.0018). Additionally, this composite symptom score showed the best predictive value for OS (c-index = 0.75). Multivariable analysis also revealed that the composite score was significantly associated with local (p = 0.044) and distant (p = 0.035) recurrence/progression. Notably, the same significant associations with OS were seen for HPV-positive only subset analysis (p < 0.01 for all symptoms). Conclusions: Quantitative patient-reported measures of dysphagia and shortness-of-breath 3-to-6 months post-treatment are significant predictors of OS and disease recurrence/progression in OPC patients and in HPV-positive OPC only.